HUBUNGAN KONSEP DIRI DENGAN TINGKAT KECEMASAN PASIEN ULKUS DIABETIK TIPE 2 - Bintang Hartati; Dady Hidayah Damanik; Aslidar Aslidar; Ninda Wahyuni (Indonesian Trust Health Journal, 2026)
A diabetic ulcer is a chronic complication of diabetes mellitus manifesting as an open wound on the skin surface, potentially accompanied by localized tissue necrosis. Anxiety is an unpleasant and distressing feeling of fear, often accompanied by physiological symptoms. This study employed a quantitative, analytical survey design using a cross-sectional approach to determine the relationship between self-concept and anxiety levels in patients type 2 diabetes mellitus diabetic ulcers. The results showed that the majority of patients (87 individuals or 58%) possessed a positive self-concept. The majority (52 individuals or 34.7%) experienced a moderate level of anxiety. A significant relationship was found between self-concept and anxiety levels in patients with type 2 diabetes mellitus and diabetic ulcers; the Chi-Square test yielded a p-value of 0.000 (p < 0.05). It is recommended that healthcare institutions continue to enhance health education regarding self-concept to help manage anxiety levels in patients with diabetic ulcers. Educational institutions are encouraged to further research and expand the body of knowledge and insight regarding self-concept and anxiety in these patients to support future studies. Abstrak Ulkus diabetikum adalah salah satu bentuk komplikasi kronik diabetes mellitus berupa luka terbuka pada permukaan kulit yang dapat disertai adanya kematian jaringan setempat. Kecemasan adalah suatu perasaan takut yang tidak menyenangkan dan tidak dapat dibenarkan yang sering disertai dengan gejala fisiologis. Jenis penelitian ini adalah kuantitatif desain penelitian survei analitik. Pendekatan yang digunakan adalah cross sectional study dengan tujuan untuk mengetahui hubungan konsep dri dengan tingkat kecemasan pasien ulkus diabetik DM tipe 2. Hasil penelitian menunjukkan bahwa mayoritas konsep diri pasien ulkus diabetik adalah baik yaitu 87 orang (58%). Mayoritas tingkat kecemasan pasien ulkus diabetik adalah sedang yaitu 52 orang (34,7%). Ada hubungan signifikan antara konsep diri dengan tingkat kecemasan pada Pasien ulkus diabetik DM tipe 2, hasil uji Chi Square didapatkan nilai p=0,000 (p<0.05). Disarankan kepada instansi kesehatan, diharapkan agar terus meningkatkan penyuluhan kesehatan tentang konsep diri sehingga dapat mengontrol tingkat kecemasan pada pasien ulkus diabetik. Kepada Instansi Pendidikan diharapkan agar terus meningkatkan kajian untuk memperluas khasanah keilmuan dan wawasan tentang konsep diri dan kecemasan pasien ulkus diabetik untuk mendukung penelitian masa yang akan datang.